Elucidation of asthma phenotypes in atopic teenagers through parallel immunophenotypic and clinical profiling - Hollams, E.; Deverell, M.; Serralha, M.; Suriyaarachchi, D.; Parsons, F.; Zhang, Guicheng; de Klerk, N.; Holt, B.; Ladyman, C.; Sadowska, A.; Rowe, J.; Loh, R.; et al. (Mosby, Inc., 2009)
Background: Current treatment strategies for asthma in teenagers derive primarily from information on chronic disease in adults. More detailed understanding of risk factors related to teenage asthma might aid in the development of improved preventive and treatment strategies for this age group. Objective: We sought to identify biomarkers associated with asthma phenotypes in teenagers, particularly atopic asthma, and to identify markers that aid in discriminating between atopic subjects at high versus low risk of asthma. Methods: We studied 1380 unselected 14-year-olds and collected data on clinical history, allergic sensitization, and respiratory and immunoinflammatory function. The latter comprised measurements of circulating inflammatory markers and in vitro innate and adaptive immune functions, including house dust mite T-cell responses. We integrated the data into regression models to identify variables most strongly associated with asthma risk and severity among atopic subjects. Results: Eight hundred twenty-seven subjects were atopic, 140 subjects were asthmatic, and 81% of asthmatic subjects were also atopic. We identified asthma risk variables related to atopy intensity, including specific IgE and eosinophil levels, plus an additional series external to the TH2 cascade but that modified risk only in atopic subjects, including IFN-?, IL-10, and IL-12 responses and neutrophil numbers in blood. Moreover, bronchial hyperresponsiveness was associated strongly with atopic but not nonatopic asthma, and the bronchial hyperresponsiveness risk profile was itself dominated by atopy-associated variables. Conclusions: Asthma in teenagers is predominantly driven by atopy acting in concert with a second tier of TH2-independent immunoinflammatory mechanisms, which contribute to pathogenesis only against the background of pre-existing inhalant allergy. © 2009 American Academy of Allergy, Asthma & Immunology.